A Novel Chimney Approach for Management of Horseshoe Kidney During EVAR. (2016) - Sharma, K.; Babrowski, T.; Milner, R.
Abstract : Introduction: Abdominal aortic aneurysms (AAAs) with coexisting horseshoe kidney (HSK) can be difficult to repair, with variable blood supply from the aorta and iliac/mesenteric vessels. Endovascular aneurysm repair (EVAR) has become a popular, less invasive approach to aneurysm care, and a chimney approach to EVAR (ChEVAR) has expanded its use to more complex anatomy. It is mandatory to maintain adequate perfusion to the HSK and visceral branches as part of the treatment of an AAA. Report: A 61-year-old male with an HSK was incidentally found to have an infrarenal AAA that measured 6 cm on a non-contrast computed tomography (CT) scan performed originally for a urologic complaint. A diagnostic angiogram was performed to define arterial anatomy and he was found to have a large inferior mesenteric artery (IMA) arising 1 cm above the level of the aneurysm. ChEVAR was performed to preserve the IMA and flow to the HSK with a completion angiogram revealing patent renal arteries, IMA, and no evidence of an endoleak. Follow-up CT imaging demonstrated a Type II endoleak that resolved upon partial nephrectomy for a right-sided transitional cell carcinoma with resection of the arterial blood supply feeding the Type II endoleak. Discussion: IMA preservation via ChEVAR is technically feasible and was crucial to preserve blood supply via the IMA to the HSK. Partial nephrectomy treated the transitional cell carcinoma and resolved the Type II endoleak requiring no additional endovascular intervention. A unique treatment course demonstrated the benefits of less invasive interventions when repairing AAA with an HSK. Highlights: Complex anatomy such as horseshoe kidney with AAA is difficult to fix. Open repair has anatomic barriers, so EVAR is a technically safer option. Chimney EVAR is feasible for perfusion of a horseshoe kidney via the IMA. Type II endoleak following EVAR resolved because of the partial nephrectomy.